Association between family functions and antenatal depression symptoms: a cross-sectional study among pregnant women in urban communities of Hengyang city, China - Huilan Xu; Zhao Hu; Xidi Zhu; Baohua Zheng; Yunhan Yu; Wensu Zhou; Shilin Yin (BMJ Open)
Objective To explore the prevalence of depressive symptoms among women in late pregnancy, and assess mediating effect of self-efficacy in the association between family functions and the antenatal depressive symptoms.Design Community-based, cross-sectional study was conducted among women during the third trimester of pregnancy.Setting This study was conducted among pregnant women registered at community health service centres of urban Hengyang City, China from July to October 2019.Participants 813 people were selected from 14 communities by multi-staged cluster random sampling method.Main outcome measures The Family Adaptation Partnership Growth Affection and Resolve Index, the General Self-efficacy Scale and Patient Health Questionnaire were used to access family functions, self-efficacy and antenatal depression symptoms, respectively.Results In this study, 9.2% pregnant women reported the symptoms of antenatal depression (95 CI% 7.2% to 11.2%). After adjustment, the results showed that severe family dysfunction (adjusted OR, AOR 3.67; 95% CI 1.88 to 7.14) and low level of self-efficacy (AOR 3.16; 95% CI 1.37 to 7.27) were associated with antenatal depressive symptoms (p<0.05). Furthermore, self-efficacy level partially mediated the association between family functions and antenatal depressive symptoms(β=−0.05, 95% CI −0.07 to −0.03, p<0.05) and the mediating effect accounted for 17.09% of the total effect.Conclusions This study reported 9.2% positive rates of antenatal depression symptoms among women in the third trimester of pregnancy in Hengyang city, China. The mediating effect of self-efficacy on the association between family functions and antenatal depression symptoms among women in the third trimester of pregnancy was found in this study, which provide a theoretical basis to maternal and child health personnel to identify high-risk pregnant women and take targeted intervention for them.